TINGKAT KETAHANAN PANGAN RUMAH TANGGA PETANI PADI SAWAH DI KELURAHAN TANI AMAN KECAMATAN LOA JANAN ILIR KOTA SAMARINDA (The Food Security Level of Paddy Farmer Household in Tani Aman Urban Village, Loa Janan Ilir Subcity, Samarinda City) - NURHADINAH NURHADINAH; MURSIDAH MURSIDAH; NIKE WIDURI (Universitas Mulawarman (University of Mulawarman), 2019)
The purpose of this study was to know the food security level of paddy farmers household in Tani Aman Urban Village, Loa Janan Ilir Subdistrict. The sampling method was proportional random sampling with a total samples of 40 respondents. The food security level of paddy farmers household was known by using descriptive analysis. The results of this study show the increasing production in the medium category with total score of 204 and the average of 5.1, food reserve in medium category with total score of 257 with average of 6.42, food aid in the low category with total score of 244 with an average of 6.1.The food distribution includes economic access in the high category with a total score of 309 with an average of 7.72, physical access in the high category with total score of 476 with an average of 11.9, social access is in the moderate category score with total score of 312 with an average of 7.8. The indicator of food absorption includes food security in the high category with total score of 592 with an average of 14.8, and food diversification in the low category with total total of 183 with an average of 4.57.